Revisiting Badiou's Theory of the Political Subject. - Rech, Walter (Theoria: A Journal of Social & Political Theory, 2024)
This article argues that Alain Badiou's theory of the subject offers conceptual resources that help make sense of ordinary life-experiences of 'evental moments' and enable the critique of hypertrophic forms of political or corporate agency. The article identifies a set of ideas through which Badiou's philosophy contributes to much-needed emancipatory thinking today. As it investigates the notions of horlieu and the event, the article stresses that true political change requires the emancipation of the 'quasi-totality', something that 'reactive' political or corporate subjects would not be able to deliver. The piece emphasises that, for Badiou, universalist equality is the indispensable game-changer of politics, and that every single person can contribute to genuinely egalitarian projects. In Badiou's view, there are no meta-subjects and meta-events. Everyone can experience truth in their lives.